(3TQM GdYRi aj GdJUQjas - (3eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj, SYO GdOjf , J (B793 (3g` s; (3YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH GdNRQLj GdRfLGfj,J (B655 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ GdJaJGRGfi GdeNJUQ GdPi Ufag GdRfLGfi s
(3BNQgG (B:s
(3JeJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B216s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1139s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdUQas